Fracture mechanics of cementitious materials - Cotterell, Brian (Blackie Academic & Professional, 1996)
Summary: "The application of fracture mechanics to cementitious materials allows the investigation of many important factors relating to the durability of these materials. This new book provides a comprehensive and readable exposition of this subject and is written by two of the world's foremost experts."